Solar-Powered Flood Monitoring System with IoT - Nasir, Nur Adli; Ab. Rahman, Munirah; Tukiran, Zarina; Ismail, Nurulhuda (Evolution in Electrical and Electronic Engineering, 2023)
Flood is one of the most common environmental disasters on the east coast of Malaysia. Floods can be affected by the local, or very large neighborhoods or communities in the entire river basin. Floods can happen slowly, but sometimes flash floods can occur very fast. In some flood areas especially in rural places, there is still no establishment of a flood warning system to give warn the local villages about upcoming floods. For other places with onsite measurement river water level, the system is lacking the ability to log, send and monitor the data in real-time. In addition, the system with a battery power supply may face battery drainage issues which will affect the process of water level measurement. Therefore, a flood detection system has been developed in which capable of measuring the river level automatically. The system can log, send, and monitor data in real-time using IoT technology. The system circuit is equipped with solar panels as the power supply and can give warnings to local people about upcoming floods by using a buzzer and an Android application. Real-time flood information and warnings will allow local people to have effective preparation in facing the flood, hence minimizing the losses during the flood event.